2014
DOI: 10.1371/journal.pone.0096932
|View full text |Cite
|
Sign up to set email alerts
|

Urinary and Plasma Levels of Vasohibin-1 Can Predict Renal Functional Deterioration in Patients with Renal Disorders

Abstract: Vasohibin-1 (VASH-1) is a negative feedback regulator of angiogenesis, and a small vasohibin-binding protein (SVBP) serves as its secretory chaperone and contributes to its antiangiogenic effects. In the present study, we aimed to define the clinical significance of VASH-1 and SVBP in patients with chronic kidney disease (CKD). We recruited 67 Japanese hospitalized patients with renal disorders with (n = 45) or without (n = 22) renal biopsy samples and 10 Japanese healthy controls. We evaluated the correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 51 publications
(66 reference statements)
1
13
0
Order By: Relevance
“…A similar situation has been documented in cases of disease associated with augmented cellular stress, namely, chronic renal disease (CKD) 62,63) . Importantly, one study determined the concentrations of VASH1 in CKD patients using ELISA; the results revealed that the plasma levels of VASH1 positively correlate with tracheal administration of adenoviral vectors encoding human VASH1 (AdhVASH1), paraquat-induced acute lung injury is almost completely prevented.…”
Section: Sirtuin1 (Sirt1)supporting
confidence: 57%
See 3 more Smart Citations
“…A similar situation has been documented in cases of disease associated with augmented cellular stress, namely, chronic renal disease (CKD) 62,63) . Importantly, one study determined the concentrations of VASH1 in CKD patients using ELISA; the results revealed that the plasma levels of VASH1 positively correlate with tracheal administration of adenoviral vectors encoding human VASH1 (AdhVASH1), paraquat-induced acute lung injury is almost completely prevented.…”
Section: Sirtuin1 (Sirt1)supporting
confidence: 57%
“…This disorder was also found to be associated with glomerular basement membrane thickening and a reduction in the slit diaphragm density. Furthermore, renal hypertrophy and the glomerular accumulation of the mesangial matrix and type IV collagen are exacerbated in diabetic VASH1 ( / ) mice versus their diabetic wild-type littermates 38) .…”
Section: Defensive Role In the Vascular Wallmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, urinary and plasma levels of VASH1 were reported to be useful for prediction of renal functional deterioration in patients with chronic renal disease. 33 Because VASH1 was associated with progression and resistance to sunitinib treatment of ccRCCs, quantification of VASH1 expression by RNA-based detection and/or liquid biopsy specimen using urine samples would be an easier method to predict the disease progression and useful for the choice of molecular targeted therapy in the future.…”
Section: Vash1 Expression In Rcc S Mikami Et Almentioning
confidence: 99%